2012
DOI: 10.2169/internalmedicine.51.7056
|View full text |Cite
|
Sign up to set email alerts
|

Physical Signs of Dehydration in the Elderly

Abstract: Objective Dehydration is a common condition and frequent cause of hospitalization in older people, despite the caregiver's high attention in attempt to avoid its occurrence. In this study, various physical signs were examined as clinical signs of dehydration in elderly. Methods A prospective observational study was conducted in an acute care teaching hospital. Consecutive elderly patients who were admitted to the Department of Medicine were evaluated. Dehydration was defined as a calculated serum osmolality ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Despite the general awareness of the importance of this problem among medical staff, very often, older patients who are dehydrated are not being identified, or their hydration status is misdiagnosed [13,14]. Making a proper diagnosis is often a challenge, mainly because signs and symptoms that are usually ascribed to dehydration have debatable diagnostic value in the older population [15,16]. Untreated dehydration negatively affects health and wellbeing, and significantly increases mortality rates of hospitalized older patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the general awareness of the importance of this problem among medical staff, very often, older patients who are dehydrated are not being identified, or their hydration status is misdiagnosed [13,14]. Making a proper diagnosis is often a challenge, mainly because signs and symptoms that are usually ascribed to dehydration have debatable diagnostic value in the older population [15,16]. Untreated dehydration negatively affects health and wellbeing, and significantly increases mortality rates of hospitalized older patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Physical signs of dehydration in this population show poor sensitivity. In the case of patients aged 65 years or older, admitted to the teaching hospital in Japan due to an acute medical condition, the sensitivity of physical signs of dehydration-such as dry mouth; sunken eyes; decreased skin turgor; dry axilla; decreased consciousness level; and delayed capillary refill time-was equal to 56% (for dry axilla) or lower [9]. The diagnostic accuracy of commonly used signs and symptoms of dehydration (such as self-reported feelings of thirst and well-being; mouth, skin, and axillary dryness; skin turgor; sunken eyes; capillary refill; blood pressure upon resting and after standing; body temperature; and pulse rate) was also low in the study performed in care home residents aged ≥ 65 years in the United Kingdom [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, skin elasticity decreases with ageing that affects skin turgor. In their prospective observational studies, Fortes et al (2015) and Shimizu et al (2012) also found that physical signs and symptoms, including low systolic blood pressure, tachycardia, dry mucous membranes or axilla, sunken eyes, and poor skin turgor and capillary refill time, have poor sensitivity as indicators of dehydration in older persons. Hoyle, Chua, and Soiza (2011) questioned the clinical utility of physical assessment in identifying dehydration due to fair interobserver agreement.…”
Section: Introductionmentioning
confidence: 99%